2022 International Conference on Robotics and Automation (ICRA) 2022
DOI: 10.1109/icra46639.2022.9812273
|View full text |Cite
|
Sign up to set email alerts
|

Failure is an option: Task and Motion Planning with Failing Executions

Abstract: Task and motion planning represents a powerful set of hybrid planning methods that combine reasoning over discrete task domains and continuous motion generation. Traditional reasoning necessitates task domain models and enough information to ground actions to motion planning queries. Gaps in this knowledge often arise from sources like occlusion or imprecise modeling. This work generates task and motion plans that include actions cannot be fully grounded at planning time. During execution, such an action is ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…A recent review on robot failure by Liu et al (2023) showed that most of the research studies focus on operational failures decoupled from system failures. Pan et al (2022) looked at failures in task and motion and adapted their approaches based on the actions that failed during task execution. However, the hardware failures are not explicitly captured or triggered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on robot failure by Liu et al (2023) showed that most of the research studies focus on operational failures decoupled from system failures. Pan et al (2022) looked at failures in task and motion and adapted their approaches based on the actions that failed during task execution. However, the hardware failures are not explicitly captured or triggered.…”
Section: Introductionmentioning
confidence: 99%
“…On the adaptive modeling perspective, many recent works have focused on Bayesian inference ( Hammond et al, 2019) , adapting the underlying world transition models ( Pan et al, 2022) and learning the task feasibility model to deal with uncertainties during execution ( Noseworthy et al, 2021) . In terms of application, most of the focus has been on systems recovery via resolving programmatic deadlocks in the service robots ( Das et al, 2021) ; Hammond et al, 2019) or, in the real world, mostly on grasping and bin-picking problems.…”
Section: Introductionmentioning
confidence: 99%